PERANCANGAN MESIN EXTRUDER FILAMEN 3D PRINTING BERBAHAN SAMPAH PLASTIK KAPASITAS 40 KG/JAM - Santoso, Deri Teguh; Saputra, Fadillah Anugrah; Sari, Rianita Puspa (Machine : Jurnal Teknik Mesin, 2024)
Plastics have experienced a rapid increase in production over the last 70 years. Initially, in 1950, the world only produced 2 million tons, and now production is more than 450 million tons. Around a quarter of plastic waste is thrown away and needs to be appropriately managed, namely around 82 million tons. In other words, the waste is not disposed of in a proper disposal site, not recycled or burned. This research underwent several stages: literature study, data collection, extruder design, machine element calculations, analysis and discussion. Six types of materials will be used as objects for selecting extruder materials, including SS 410, SS 422, AISI 4140, AISI 4340, AISI 1144, and AISI 1045. Planning is carried out on the machine elements so that von Misses stress and deflection values ​​are obtained to determine the appropriate values. Extruder design planning. It was concluded that the highest Von Misses Stress value was obtained for all materials with variations in material length and width, namely 700 and 45 mm. The higher the length and diameter dimensions, the higher the von Misses stress value. The highest deflection value was obtained on Stainless Steel 410 material with variations in length and width of the material, namely 700 and 45 mm. The higher the length dimension of a material, the higher the deflection value.